The Effect of Audit Committee Effectiveness and Potential Fraudulent Financial Statements - Deviana Purwiyanti; Herry Laksito (Politeknik Negeri Madiun, 2022)
This study aims to determine the relationship formed between the effectiveness of the audit committee and fraudulent financial statements. The effectiveness of the audit committee in this study will be proxied through the expertise of the audit committee members, the frequency of audit committee meetings, the size of the audit committee, and also the tenure of the audit committee members. Financial statement fraud in this study will be measured using the Beneish M-Score formula. This study uses financial sector companies listed on the Indonesia Stock Exchange during the 2019-2020 period as the object of research. The population used in this study was 174 companies. The test results in this study show that the expertise of the audit committee members, frequency of audit committee meetings and the tenure of the audit committee members have a negative and significant influence on the occurrence of fraudulent financial statements in the company.